Complex variables : introduction and applications - Ablowitz, Mark J. (Cambridge University Press, 2003)
Complex variables provide powerful methods for attacking problems that can be very difficult to solve in any other way, and it is the aim of this book to provide a thorough grounding in these methods and their application. Part I of this text provides an introduction to the subject, including analytic functions, integration, series, and residue calculus and also includes transform methods, ODEs in the complex plane, and numerical methods. Part II contains conformal mappings, asymptotic expansions, and the study of Riemann-Hilbert problems. The authors provide an extensive array of applications, illustrative examples and homework exercises. This 2003 edition was improved throughout and is ideal for use in undergraduate and introductory graduate level courses in complex variables.
Keywords: Functions of complex variables.; Fonctions d'une variable complexe.; MATHEMATICS -- Complex Analysis.; Functions of complex variables; Funktionentheorie; Funções de várias variáveis complexas.; Matemática.; Electronic books.